Observational, multicenter study of the incidence and treatment patterns of acquired aplastic anemia in four national reference hospitals in Peru - La Torre-Matuk, Alejandra (2021)
Objectives: To describe the frequency of acquired Aplastic Anemia (AA) in four main referral hospitals, as well as the treatment patterns of this disease in Peru. Methods: An observational, multicenter, retrospective phase for 2016, and prospective phase during 2017, was carried out in the Arzobispo Loayza, Cayetano Heredia, Edgardo Rebagliati Martins and Carlos Alberto Seguín Escobedo national hospitals. Results: 48 patients were recruited, 21 (43,8%) had severe anemia, 26 (54,2%) were not exposed to any toxic, but 6 (12,5%) were exposed to organophosphates. Twenty-five of forty-eight patients (52,1%) began treatment with the methylprednisolone + cyclosporine + anti-thymocyte globulin regimen (rabbit or horse). The median time from diagnosis to the start of treatment was 28,5 days. Only 3 (6,25%) patients underwent bone marrow transplantation as initial treatment. Eleven (22,9%) died during the study. The estimated prevalence and incidence are 9 and 5 per million, respectively. Conclusions: The time from diagnosis to start of treatment was long. The most common serious adverse events were infectious, as has been reported in similar studies. Almost half of patients did not receive firstline therapy. Mortality at 12 months of follow-up was high compared to other studies.